Generation of a gene-corrected isogenic human iPS cell line (CSUASOi006-A-2) from a retinitis pigmentosa patient using CRISPR/Cas9 technology - Chen, Hang; Liang, Yuqin; Liang, Yuan; Chen, Yuexi; Li, Xiaoxue; Zhang, Ruting; Duan, Chunwen; Li, Wenwei; Cui, Zekai; Gu, Jianing; Ding, Chengcheng; Sun, Xihao; et al. (Stem cell research, 2025)
Retinitis pigmentosa (RP) is a heterogeneous group of hereditary eye disorders characterized by a progressive degeneration of the light-sensing photoreceptor cells in the retina. Currently, there are no effective treatments. In a previous study, we generated a human induced pluripotent stem (iPS) cell line (CSUASOi006-A) from an RP patient carrying a PRPF8 (c.C5792T) mutation. In this study, we corrected the c.5792C > T mutation in the PRPF8 gene using CRISPR/Cas9 technology and generated an isogenic control cell line (CSUASOi006-A-2). This provides an important cellular resource for RP research.